Characterization of Sleep Structure and Autonomic Dysfunction in REM Sleep Behavior Disorder - Nicla Mandas; Maximiliano Mollura; Giulia Baldazzi; Parisa Sattar; Maria Mura; Elisa Casaglia; Michela Figorilli; Laura Giorgetti; Pietro Mattioli; Francesco Calizzano; Francesco Fama; Dario Arnaldi; et al. (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: REM Sleep Behavior Disorder (RBD) is a REM parasomnia that is associated to high risk of developing α-synucleinopathies, as Parkinson's disease (PD) or dementia with Lewy bodies, over time. This study aims at investigating the presence of autonomic dysfunctions in RBD subjects, with and without PD, by assessing their sleep structure and autonomous nervous system activity along the different sleep stages. Methods: To this aim, an innovative framework combining a sleep transition model, by Markov chains, with an instantaneous assessment of autonomic state dynamics by statistical modeling of heart rate variability (HRV) dynamics through a point-process approach, was introduced. Results: In general, RBD groups showed lower HRV than controls across all sleep stages, as well as higher probabilities of transitioning towards lighter sleep stages. Subjects also affected by PD present an even lower HRV, but better sleep continuity. Conclusions: RBD patients suffer from sleep fragmentation and overall autonomic dysfunction, mainly due to lower autonomic activation across all sleep stages. Coexistence of PD seems to improve sleep quality, possibly due to a sleep-related relief of their symptoms.